2022
DOI: 10.15388/infedu.2023.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Scratch-based activities on 4th-grade students’ computational thinking skills

Abstract: Computational Thinking (CT) has emerged in recent years as a thematic trend in education in many countries. initiatives have been developed for its inclusion in school curricula. There are many pedagogical strategies to promote the development of elementary school students’ CT skills and knowledge. Unplugged learning tasks, block-based programming projects, and educational robotics are 3 of the most used strategies. This paper aimed to analyze the effect of Scratch-based activities, developed during one schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The usage of block-based programming activities had a positive effect on the pre-service teachers' results. Activities involving problem-solving or creation of projects like simple games or animations have an evident effect on the level of the computational thinking skills not only promote the development of computational thinking skills but also contribute to the application of knowledge from other curricular areas (Piedade & Dorotea, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usage of block-based programming activities had a positive effect on the pre-service teachers' results. Activities involving problem-solving or creation of projects like simple games or animations have an evident effect on the level of the computational thinking skills not only promote the development of computational thinking skills but also contribute to the application of knowledge from other curricular areas (Piedade & Dorotea, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…There are always 4 possible answers, but only one of them is correct. It should be noted that the BCTt does not assess competencies, but rather allows us to measure the students' knowledge and skills regarding concepts associated with Computational thinking (Piedade & Dorotea, 2023). We'll refer to them as computational thinking skills in this paper.…”
Section: Assessment Of Computational Thinking Skillsmentioning
confidence: 99%
“…Scratch is a visual, block-based programming language used by novices to learn computer-related concepts; it also provides an interactive media-rich, user-friendly environment for users to develop their projects collaboratively in the form of animations, games, and stories. 3 , 13 , 23 , 25 The lessons, including lectures and practice, were delivered in a computer classroom.…”
Section: Methodsmentioning
confidence: 99%
“…4,8,24 The advantages of Scratch for programming novices are evidential. Many researchers have identified positive results in learning, including programming knowledge and achievement, 8,23,25 computational thinking skills, 23,25 a positive attitude toward programming, 4,6,13,23 and learning motivation. 8 Scherer et al 22 meta-analyzed previous studies and found that interventions focusing on visualization through Scratch are especially effective because visual programming languages may reduce the cognitive load associated with reading, understanding, and creating code.…”
Section: Scratch Programmingmentioning
confidence: 99%
“…Aside from its entertainment value, Scratch is a powerful tool for developing problem-solving and criticalthinking skills. It has been proven to enhance comprehension in various subjects (Kalelioglu & Gulbahar, 2014;Piedade & Dorotea, 2022). Educational institutions, from primary schools to universities and after-school programs, have embraced Scratch as a way to introduce students to the exciting world of coding.…”
Section: Introductionmentioning
confidence: 99%